Distribution and population biology of helmet crab Telmessus cheiragonus (Decapoda: Cheiragonidae) in the northern Okhotsk Sea - D. V. Artemenkov; Yu. V. Ivankovich; O. Yu. Borilko; S. I. Moiseev; D. O. Sologub; P. Yu. Ivanov; A. V. Kharitonov; S. V. Klinushkin; A. N. Deminov; T. B. Morozov (Известия ТИНРО, 2025)
Helmet crab Telmessus cheiragonus is a potentially important commercial species dwelling in the Far Eastern Seas of Russia. Biology of its populations in the areas of Shantar Islands and West Kamchatka (northern Okhotsk Sea) is described for the first time, with particular attention to the larval cycle, growth, and sex and size structure. On the shelf of West Kamchatka, the densest aggregations are formed in June, for males and females respectively at the depths of 13–55 m (on average 21.3 ± 3.2 m) under temperature 2.8–6.5 ºC (4.8 ± 0.3 ºC) and at the depths of 16–19 m (17.3 ± 0.9 m) under temperature 4.3–5.2 ºC (4.7 ± 0.3 ºC). At Shantar Islands, the densest aggregations are observed in September at the depths of 13–23 m (18.0 ± 4.8 m) under temperature 8.3–15.5 ºС (11.9 ± 3.6 ºС). For the group growth of crabs at West Kamchatka, the maximum carapace width of females and males is estimated as 66.3 and 82.6 mm, respectively, that is less of this parameter for the males caught to the north and  northwest of Shantar Islands (86.7 mm). Moulting of helmet crab at West Kamchatka occurs in May-June, whereas the longer moult period is expected at Shantar Islands — from May to August. The mean size of sexual maturity is 40.6 mm for females and 40.3 mm for males in the population at West Kamchatka; the crab males at Shantal Islands develop slower and reach sexual maturity at the carapace width of 42.1 mm, on average.